MENGUKUR DERAJAT KEISLAMAN EKONOMI DAN FAKTOR PENDORONGNYA: STUDI KASUS PROVINSI DI INDONESIA - ALI RAMA (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The study aims to rank the degree of economic Islamicity for all provinces in Indonesia using ‘economic islamicity index’. Other than that, the study investigates the impacts of economic performances, market share of Islamic banking and human development to economic Islamicity performance. To achieve the purposes, the study employs index method, descriptif analisis,correlation and regression models. The study finds that Indonesia as Muslim majority population has lower degree of Islamicity, particularly in the aspect of economic Islamicity. The average performances of all provinces are in middle level which is ranging between 30-40 points. The result indicates that the overall performances of economic Islamicity for all provinces in Indonesia are relatively same, there is no signficant gap between them. The statistical findings confirm that economic performances (economic growth and income per capita) and humand development are statistically significant in affecting the index performances. Thus, economic and human development are among the keys achieving the purposes of the Islamic economic system.